2006
DOI: 10.1002/jcb.21175
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in medfly hemocytes is regulated during pupariation through FAK, Src, ERK, PI‐3K p85a, and Akt survival signaling

Abstract: Focal adhesion kinase (FAK) and its downstream signaling targets are implicated in the process of apoptosis induced by external stimuli, in several mammalian systems. In this report, we demonstrate, that medfly (Ceratitis capitata) hemocytes do undergo apoptosis during larval development. In particular, we show using Western blot, ELISA and flow cytometry analysis, that FAK expression silencing in transfected by FAK double-stranded RNA (dsRNA) hemocytes, enhances twofold hemocyte apoptosis, by signaling throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…FAK is considered to be a component of central importance because it is known to associate with multiple cell surface receptors (integrins, growth factor receptors and G‐protein‐linked receptors) and signalling proteins through which it can modulate the activity of several intracellular signalling pathways 26,38 . FAK is a family of non‐receptor and non‐membrane‐associated tyrosine kinases, which have been implicated in controlling several cellular functions, including cell spreading, migration, apoptosis and cell survival 25,26 . The present data show that E. coli , S. aureus , latex beads, LPS, FN or RGD peptides phosphorylate FAK at Y397 rapidly and considerably (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…FAK is considered to be a component of central importance because it is known to associate with multiple cell surface receptors (integrins, growth factor receptors and G‐protein‐linked receptors) and signalling proteins through which it can modulate the activity of several intracellular signalling pathways 26,38 . FAK is a family of non‐receptor and non‐membrane‐associated tyrosine kinases, which have been implicated in controlling several cellular functions, including cell spreading, migration, apoptosis and cell survival 25,26 . The present data show that E. coli , S. aureus , latex beads, LPS, FN or RGD peptides phosphorylate FAK at Y397 rapidly and considerably (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…To explore the functional role of FAK in the uptake of Gram‐negative bacteria ( E. coli ), Gram‐positive bacteria ( S. aureus ), abiotic components (latex beads) or small molecules (LPS) as well, dsRNA corresponding to Drosophila FAK was transfected into medfly haemocytes of wandering stage larvae as described previously to specifically deplete FAK expression 25 . As reported in this study, dsRNA corresponding to Drosophila FAK works in medfly haemocytes bringing about 55% diminution of FAK expression 25 . The depletion was only partial, evidently, because of the short‐term incubations, as the viability of haemocytes decreases in long‐term incubations.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular attachment to the extracellular matrix is mediated via the association of integrins with specific extracellular matrix ligands, such as Von willebrand factor (VWF), COMP, and cilinical spectrum of type IV collagen (COL4A), as integrins do not themselves possess a kinase domain or enzymatic activity but rely on those ligands to interact with the actin cytoskeleton . More than that, FAK, a major integrin‐dependent tyrosine phosphorylated protein, could also get to be involved in the control of cell extracellular interactions . The ability of these proteins to bind with actin‐alpha and talin to integrin cytoplasmic tails, and the subsequent recruitment of the actin‐binding protein vinculin, could contribute to link adhesion complexes to the actin cytoskeleton .…”
Section: Discussionmentioning
confidence: 99%
“…[27] More than that, FAK, a major integrin-dependent tyrosine phosphorylated protein, could also get to be involved in the control of cell extracellular interactions. [28] The ability of these proteins to bind with actin-alpha and talin to integrin cytoplasmic tails, and the subsequent recruitment of the actin-binding protein vinculin, could contribute to link adhesion complexes to the actin cytoskeleton. [29] The presence of actin in the sperm head in acrosomal, equatorial, postacrosomal regions and tail, and the occurrence of actin polymerization during sperm capacitation manifested its significance for sperm motility and fertilization ability.…”
Section: Discussionmentioning
confidence: 99%
“…GA inhibited the translocation of NF-κB from the cytosol to the nucleus ( (Tyr 416) may act on PI-3K/AKT and Ras/ERK1/2 cascades impacting signaling (26,27). It was reported that FAK/Src complex allows Src to phosphorylate FAK and then to interact with GRB2 and activation of the Ras-ERK signaling pathway (28).…”
Section: Discussionmentioning
confidence: 99%